Analisis Faktor yang berhubungan dengan Kualitas Hidup Wanita Penderita Kanker - Naomi Toulasik; Tiyas Kusumaningrum; Retnayu Pradanie (Universitas Airlangga, 2019)
Introduction: Cancer is a group of diseases characterized by uncontrolled growth and spread of abnormal cells which can cause death. Cancer has a great impact on sufferers both physically, psychologically and socially which will affect their quality of life. There are many factors that affect quality of life.Methods: This study used cross sectional design. The population of this study were all cancer patients aged ≥ 18 years in General hospital of Prof. DR. W. Z. Johannes Kupang. The sample size was 103 respondents who met the inclusion criteria. The dependent variable was the quality of life of women with cancer, while the independent variables were age, marital status, lifestyle, body mass index, cancer type and the stage of cancer. Data was collected using questionnaires. Data then analyzed using Ordinal Regression.Results: There were correlations between age (p = 0.015), marital status (p = 0,000), cancer types (p = 0.041) and stage of cancer (p = 0,000) with quality of life. There was no correlation between lifestyle and body mass index with quality of life.Conclusion: Quality of life of women with cancer are influenced by age, marital status, type of cancer and stage of cancer. Further researchers are advised to examine the relation between psychological, physical environmental, and social environmental factors to the quality of life of women with cancer.